THE SIGNIFIER AS RUINS - Kangelaris, Fotis (Design/Arts/Culture, 2020)
Even though the seduction of ruins seems to be coming from a nostalgia for the past which, possibly, refers to the lived experience (Dasein) of youth, of glory and as a result to the vanity of the human creation, to the vanity of life itself, even if we consider ruins as a resistance and victory against time and of this against this very vanity, however, this perception for ruins is nothing but a concealment from the glance of the relation “thing”-signifier and of the way that the “thing” dictates the signifier. Ruins as a regression of the existence towards non-existence, of creativity towards fall, demonstrate the signifier as flowing from the “thing”, the Logos from ineffable, the image from unimagined, of “something” from “nothing”, art itself as a reaction of avoidance of chaos. Essentially, ruins demonstrate meaning as a reaction to “nothing”, for which “nothing” the meaning as ruins regresses when the reason of resistance disappears. Ruins on the way to “nothing”, a step before their absolute disappearance and their return to the protogenic materials of nature from which, besides, they come, that is the fall and crash of the meaning, allow a quick look over the origin of the meaning without the glance being in danger from the emergence of the absolute “nothing” as an origin of the meaning. Ruins attract us because they disclose while at the same time appeal to us because they conceal the void of the “thing” as a descent of the rational world.